Faktor- Faktor yang Mempengaruhi Respon Petani Ternak dalam Budidaya Kerbau sebagai Usaha Tetap - floriandi, A; Nurcholis, Nurcholis; Muchlis, D; Salamony, S M; Andari, G (MuJAgri: Musamus Journal of Agribusiness, 2020)
Merauke Regency has very good natural potential for the development of agricultural businesses, especially in the livestock sector. The process of improving the livestock sector has been supported by the government, namely a raised livestock program that aims to support the food needs of animal origin can be met from local procurement, one of which is buffalo cattle. The area in Merauke Regency which has quite a large buffalo population is the Kurik District with a total of 144 buffaloes. This study covers all districts in curik which are explorative in nature which are used to collect preliminary data, research data includes quantitative and qualitative data and promer and skunde data. Data analysis used in this study is descriptive analysis. The results showed that 17.39% of livestock farmers strongly agreed that buffalo cattle could be used as a permanent business, while 56.52% of livestock farmers did not agree if buffaloes were used as permanent businesses and 26.09% of livestock farmers did not agree. This is because buffalo livestock farmers only keep buffalo cattle in small quantities and only as savings or savings and grazing land which is increasingly diminishing because it is converted into agricultural land. The conclusion from this study is that not all buffalo breeders are willing to make their business a permanent business, and still rely on businesses in the field of food crops. Keywords: buffalo cultivation; permanent business; response